Kajian Sub Sektor Ekonomi Potensial Dalam Mendukung Fungsi Kota Cilegon - Supratignyo Aji; Endang Herdiansyah; Cinthia Nurry Haffiyan (Jurnal Planologi Unpas, 2015)
This study was directed to assess the potential sectors in supporting the function of the town there are three criteria set which includes the role of the economic structure, the economic base, changes in economic structure are viewed by using the GDP variable Cilegon. These criteria include each of the two sub-criteria, the criteria for the role of the economic structure consists of a contribution the GDP and the rate of GDP growth, the economic base consists of the role of a sector and doubling of a sector of activity, changes in economic structure consists of changes in the growth sectors of the economy and changes in sector activity economy. The methodology used was descriptive approach. The analysis method is to use the analysis of the economic structure, loqation question, shift share, AHP (analysis hirarcical process) and analysis of a composite index of economic petensial components and functions of the city. The results showed a potential sub-sectors contained in Cilegon include quarrying sub-sector, excluding oil and gas industry, electricity, wholesale and retail trade, sea transportation, river transportation and crossings, banks, other financial institutions and services company. Among the nine sub-sectors of the potential contained in Cilegon, sub-sectors that can support the function of Cilegon City are without oil and gas industry sub-sector, while other functions are still not able to support the functions carried Cilegon in terms of both spatial and non-spatial.